Factors contributing to innovation readiness in health care organizations: a scoping review - Monique W. van den Hoed; Ramona Backhaus; Erica de Vries; Jan P. H. Hamers; Ramon Daniëls (BMC, 2022)
Abstract Background Increasing innovation readiness of healthcare organizations is necessary to meet upcoming challenges, including population aging, staff shortages and reduced funding. Health care organizations differ in the extent to which they are innovation ready. This review aims to clarify the concept of innovation readiness and identify which factors contribute to innovation readiness in health care organizations. Methods A scoping review was conducted based on the framework from Arksey and O'Malley. PubMed/MEDLINE, CINAHL and Web of Science were searched for studies that (a) aimed to contribute to scientific knowledge about innovation readiness of health care organizations, (b) were peer-reviewed, (c) reported empirical data and (d) were written in English, Dutch or German. Factors researched in the included studies were bundled into 4 overarching main factors and 10 sub-factors. Results Of the 6,208 studies identified, 44 were included. The majority (n = 36) of the studies had been conducted since 2011 and almost half of the studies (n = 19) were performed in hospitals. Of the 44 studies, 21 researched factors contributing to innovation readiness in the implementation stage of the innovation process. The authors used a variety of words and descriptions addressing innovation readiness, with hardly any theoretical frameworks for innovation readiness presented. Four main factors and 10 sub-factors contributing to the innovation readiness of health care organizations were summarized: strategic course for innovation, climate for innovation, leadership for innovation and commitment to innovation. Climate for innovation (n = 16) was studied the most and individual commitment to innovation (n = 6) was the least studied. Conclusion Our study identified four main factors contributing to the innovation readiness of health care organizations. Research into innovation readiness of health care organizations is a rather new field. Future research could be directed towards defining the concept of innovation readiness and the development of a framework for innovation readiness. More understanding of the interplay of factors contributing to innovation readiness in all stages of the innovation process and in diverse health care settings can support health care managers to structurally embed innovation. This review contributes to the first stage of theory building on factors contributing to innovation readiness of health care organizations.